A fotografia como representação da cultura mato-grossense - Freitas, Priscila Lima (2016)
This masters research has as its theme the study of photography as a cultural representation of the State of Mato Grosso. It seeks a plausible explanation for the inherent issues in the representative capacity of photography. Wonder if a photo is able to represent the culture of a state? Any photo is capable to represent the culture of Mato Grosso. If yes, how? In order to do so, we seek to understand, through bibliographical sources, the importance of photography from its origin to the present day, its degree of cultural representativeness with the population of the state through the history traced by photography in the territory of Mato Grosso, until the mid-nineteenth century. In addition to the influences between traditional versus contemporary theoretical debates on what photography itself is and its role in society. It is proposed a methodological model of analysis applied in five representative photographs of Mato Grosso culture, based on the concepts of first and second reality of Boris Kossoy (2002), and on the spaces concepts of Ana Maria Mauad (1996). The photographs were selected according to the items in the celebratory books, buildings, form of expression, places and knowledge present in the Documentary Inventory of Material and Intangible Heritage of Mato Grosso.